The Effect of Micro, Small and Medium Enterprises on Economic Growth - Sri Juminawati; Abd. Hamid; Euis Amalia; M. Arief Mufraini; Ade Sopyan Mulazid (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Micro, small and medium enterprises (MSMEs) are declared very capable of playing a crucial role for a region, specifically as one of the drivers of regional economic growth. Micro, small and medium enterprises (MSMEs) are defined as a means to introduce regional creative products and provide business opportunities for enterprise actors in the regions. In addition, the role of micro, small and medium enterprises (MSMEs) actors is considered very vital in order to increase per capita income and improve the economy of a region. Consequently, micro, small and medium enterprises (MSMEs) are required to actively participate in developing the country’s economy. The results of the study showed that 90.1% of MSMEs provided significant effects on the rate of economic growth.